Worldview Islam dan Sikap Moderasi Muhammadiyah: Dari Dinamika Bermazhab dan Kemajuan Bermanhaj - Afifi Fauzi Abbas; Mona Eliza; Abdullah A Afifi (Perwakilan, 2024)
This article discusses the Islamic worldview and Muhammadiyah's moderation approach by highlighting the dynamics of mazhab and the progress of manhaj in Muhammadiyah Islamic thought. The discussion begins with an exploration of Muhammadiyah's religious insight which is rooted in the principles of tauhid, ijtihad, and tajdid. Furthermore, the development of Islamic thought in Muhammadiyah is studied through a scientific and contextual approach to understanding texts and social realities. Muhammadiyah's Manhaj Tarjih becomes the methodological basis for making moderate religious decisions oriented towards people's benefit. Finally, the concept of progressive moderation is associated with the development of an Islamic worldview that is balanced between spirituality and modernity. Through this approach, Muhammadiyah not only maintains the purity of Islamic teachings but also contributes to building an inclusive and progressive civilization. This article emphasizes that Muhammadiyah's progressive moderation attitude is relevant in facing contemporary challenges.